Traditional medicinal plant use in Northern Peru: tracking two thousand years of healing culture - Sharon Douglas; Bussmann Rainer W (BMC, 2006)
Abstract This paper examines the traditional use of medicinal plants in Northern Peru, with special focus on the Departments of Piura, Lambayeque, La Libertad, Cajamarca, and San Martin. Northern Peru represents the center of the old Central Andean "Health Axis," stretching from Ecuador to Bolivia. The roots of traditional healing practices in this region go at least as far back as the Moche period (AC 100-800). Although about 50% of the plants in use reported in the colonial period have disappeared from the popular pharmacopoeia, the plant knowledge of the population is much more extensive than in other parts of the Andean region. 510 plant species used for medicinal purposes were collected, identified and their vernacular names, traditional uses and applications recorded. The families best represented were Asteraceae with 69 species, Fabaceae (35), Lamiaceae (25), and Solanaceae (21). Euphorbiaceae had twelve species, and Apiaceae and Poaceae 11 species. The highest number of species was used for the treatment of "magical/ritual" ailments (207 species), followed by respiratory disorders (95), problems of the urinary tract (85), infections of female organs (66), liver ailments (61), inflammations (59), stomach problems (51) and rheumatism (45). Most of the plants used (83%) were native to Peru. Fresh plants, often collected wild, were used in two thirds of all cases, and the most common applications included the ingestion of herb decoctions or the application of plant material as poultices.